2018
DOI: 10.1001/jamasurg.2017.3398
|View full text |Cite
|
Sign up to set email alerts
|

Association of Parathyroid Hormone Level With Postthyroidectomy Hypocalcemia

Abstract: The existing literature regarding PTH levels to predict postthyroidectomy hypocalcemia is extremely heterogeneous. A single PTH threshold is not a reliable measure of hypocalcemia. Additional prospective studies controlled for timing of laboratory draws and a priori defined PTH thresholds need to be performed to ascertain the true prognostic significance of PTH in predicting postthyroidectomy hypocalcaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 74 publications
2
29
0
1
Order By: Relevance
“…Most authors currently recommend routine measurement of serum calcium and parathyroid hormone (PTH) after surgery in order to predict hypocalcaemia. Patients might therefore be classified as having hypocalcaemia, with an increase in treatments and length of hospital stay, without having any symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Most authors currently recommend routine measurement of serum calcium and parathyroid hormone (PTH) after surgery in order to predict hypocalcaemia. Patients might therefore be classified as having hypocalcaemia, with an increase in treatments and length of hospital stay, without having any symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…[18,19] We observed that most patients had a decrease in calcium during the first hours after surgery, the expected response of a parathyroid gland with a normal function would be to increase the secretion of iPTH to prevent hypocalcemia, and it may not be a false positive as previously considered. [20] This "appropriate iPTH response" is present in the patients that consequently didn't present hypocalcemia, while the patients that not only didn't increase iPTH but even decreased their concentrations, eventually presented hypocalcemia, reflecting a greater damage to the parathyroid gland and a delayed or absent response to hypocalcemia. In our study a decrease of 9.5 pg/mL or more in PTH concentrations had a good sensitivity and specificity to predict hypocalcemia, this means that patients may still have normal or detectable serum iPTH, but it is not enough to counter regulate the rapid fall in calcium.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15] The variables included a failure to reference the normal range of calcium values and the use of total, corrected or iCa. [11][12][13][14][15] The variables included a failure to reference the normal range of calcium values and the use of total, corrected or iCa.…”
Section: Discussionmentioning
confidence: 99%
“…The reported prevalence of PH after total thyroidectomy varies widely, mainly because hypocalcemia is not defined consistently. [11][12][13][14][15] The variables included a failure to reference the normal range of calcium values and the use of total, corrected or iCa. 13 Additionally, PH can be defined by biochemical blood parameters and/or by the presence of symptoms.…”
Section: Discussionmentioning
confidence: 99%